God, Modality, and Morality - Mann, William E. (New York Oxford University Press, 2015)
William E. Mann presents a philosophically defensible conception of the deity found in the Abrahamic religions. The book draws insights from such figures as Augustine, Philo, Aquinas, Leibniz, and contemporary philosophers. Unlike all other beings, God is perfect and simple. Simplicity entails that God has no physical or metaphysical parts or temporal stages. Perfection entails that God is immutable, omniscient, omnipotent, and perfectly good, having no equals or weaknesses. The book's chapters defend the coherence of these claims against various criticisms.
Include Index
Keywords: a -- God